A multi-functional zwitterionic hydrogel with unique micro-structure, high elasticity and low modulus. Issue 43 (30th September 2022) - Wang, Yueyang; Wang, Qiao; Hu, Xiaosai; He, Dan; Zhao, Juan; Sun, Guoxing
Abstract : In this article, the authors have developed an ultra-soft and tough dual-crosslinking zwitterionic hydrogel, which possesses a unique spike-like microstructure, low modulus, excellent stretchability and compressibility with self-healing properties. Abstract : Owing to their tissue-like softness and low modulus, hydrogels minimize the mechanical mismatch with biological tissues and have received wide attention as biomaterials. However, the development of soft hydrogels is often limited by their brittleness. Here, an ultra-soft and tough hydrogel based on zwitterionic poly(sulfobetaine methacrylate) (PSBMA) was designed and successfully prepared. The obtained PSBMA hydrogel exhibits a unique spike-like micro-structure, low modulus, good stretchability and excellent compressive elasticity, due to the formation of a dual-crosslinking structure. The obtained hydrogel also possesses self-healing properties and electromechanical responses to tensile and compressive deformations. Moreover, the hydrogel has good compatibility attributed to its outstanding anti-protein-adsorption properties.